Hemostatic phenotype of thrombi derived from STEMI patients on cardiovascular prevention therapy - Jeske J. K van Diemen; Bernard J Smilde; Wessel W Fuijkschot; P Stefan Biesbroek; Yolande E Appelman; Paul A. J Krijnen; Yvo M Smulders; Hans W. M Niessen; Abel Thijs (Journal of the Practice of Cardiovascular Sciences, 2019)
Introduction: Aspirin and statin therapy are the basis of cardiovascular disease (CVD) prevention therapy. Recent data have suggested new additional preventive mechanisms: both aspirin and statin exhibit anti-inflammatory effects within intracoronary thrombi. As inflammation, aggregation, and thrombosis are closely intertwined, aspirin and subsequent statin therapy might influence the hemostatic content within intracoronary thrombi. Aim: The aim of the study is to explore the spectrum of CVD prevention therapy on intracoronary thrombus composition by analyzing main hemostasis components in patients with ST-segment elevation myocardial infarction (STEMI). Materials and Methods: We performed a cross-sectional histological pilot study with intracoronary thrombi derived from STEMI patients on CVD prevention therapy without usage of another anticoagulant agent other than aspirin. They were actively matched with intracoronary thrombi in a control group derived from STEMI patients not on any therapy – without a previous CVD history – based on thrombus age (fresh), sex, and age of the participant. Immunohistochemistry was performed with primary antibodies of factor XII (F-XII), tissue plasminogen activator (tPA), and factor VII (F-VII). Results: Four of the 13 thrombi derived from patients on CVD prevention therapy were not characterized as fresh and subsequently excluded. Moreover, one participant in the patient group had to be excluded post hoc. The thrombi in the patient group had a significantly more F-XII (27.7%) and tPA (10.1%) positive area versus the controls (17.5%; 4.5%), respectively. The F-VII-positive thrombus area was similar in both groups. Conclusion: These exploratory data demonstrate an increased procoagulant F-XII and fibrinolytic tPA content within intracoronary thrombi derived from patients on CVD prevention therapy compared with controls.